Effects of Transformational Leadership on Employee Performance in Business Organizations: A Systematic Literature Review - Mahmud Mahmud; Shoalihin Shoalihin; Nurul Hayat (Brilliant International Journal Of Management And Tourism, 2023)
In the face of increasingly fierce and complex organizational competition, this allows organizations to change the management pattern strategy that is played especially in increasing optimal performance through the role of human resource management because it is human resources who have a mindset through ideas, opinions, as well as views that are not shared by other resources. Employees are human resources who hold the most important position in implementing an organisation's vision, mission and goals. Employee performance is one of the markers that need to be considered by the organization. When employees feel unmotivated at work, this will have an impact on inhibiting organizational operational activities. Therefore, one strong indicator of influencing the environment is the presence of a leader. There are many styles preferred by employees, one of which is the transformational leadership style, especially in the current digitalization era. This writing aims to understand and explore the influence of transformational leadership style on employee performance. The method used is a Systematic Literature review using secondary data, where the author collects data related to the theme, and information is taken from various Scopus-indexed journals. The results of the study suggest that the transformational leadership style can affect the performance of employees in the organization. Because employees are actively involved, they feel increased motivation, increased trust, willingness to follow philosophy, ideology, vision, and increased consequences of interesting change. They have high commitment and can see one's abilities. Employees who are inspired by transformational leadership are also more likely to immerse themselves in work, resulting in better task performance and helping behaviours that ultimately help build organizational progress